Function and molecular regulation of DWARF1 as a C-24 reductase in brassinosteroid biosynthesis in Arabidopsis. (8th February 2018) - Youn, Ji Hyun; Kim, Tae-Woo; Joo, Se-Hwan; Son, Seung-Hyun; Roh, Jeehee; Kim, Sunyoung; Kim, Tae-Wuk; Kim, Seong-Ki
Abstract : DWARF1 functions as a brassinosteroid C-24 reductase that converts 24-methylene brassinosteroids to 24-methyl brassinosteroids to regulate the endogenous level of an active brassinosteroid, castasterone, to control growth and development in Arabidopsis. Abstract: DWARF1 (DWF1) is a sterol C-24 reductase that catalyses the conversion of 24-methylenecholesterol (24-MCHR) to campesterol (CR) in Arabidopsis. A loss-of-function mutant, dwf1, showed similar phenotypic abnormalities to brassinosteroid (BR)-deficient mutants. These abnormalities were reversed in the wild-type phenotype by exogenous application of castasterone (CS) and brassinolide (BL), but not dolichosterone (DS). Accumulation of DS and decreased CS were found in quantitative analysis of endogenous BRs in dwf1. The enzyme solution prepared from dwf1 was unable to convert 6-deoxoDS to 6-deoxoCS and DS to CS, as seen in either wild-type or 35S:DWF1 transgenic plants. This suggests that DWF1 has enzyme activity not only for a sterol C-24 reductase, but also for a BR C-24 reductase that catalyses C-24 reduction of 6-deoxoDS to 6-deoxoCS and of DS to CS in Arabidopsis. Overexpression of DWF1 in a BR-deficient mutant ( det2 35S:DWF1 ) clearly rescued abnormalities found in det2, indicating that DWF1 functions in biosynthesis of active BRs in Arabidopsis. Expression of DWF1 is down-regulated by application of CS and BL and in a BR-dominant mutant, bes1-D . E-boxes in the putative promoter region of DWF1 directly bind to a BR transcription factor, BES1, implying that DWF1 expression is feedback-regulated by BR signaling via BES1. Overall, biosynthesis of 24-methylene BR is an alternative route for generating CS, which is mediated and regulated by DWF1 in Arabidopsis.